Direct Determination of the Intermolecular Potential of Kr-N2, Xe-N2 and He-SF6 form the Extended Principle of Corresponding States - Iloukhani, H.; Tavangar, Z.; K. Goharshadi, Elahe (Asian Journal of Chemistry, 2010)
A more direct semi-empirical inversion has been developed that obtains a non-parametric potential from experimental data The method is iterative and coverage rapidly once a good choice has been made for the initial starting potential. To be specific. the aim of an inverse method is to obtain the potential by considering the experimental data as a functional, instead of fitting the data to a constrained potential for having a few parameters. The interaction potentials are estimated for the Kr—N2, Xe—N2 and He—SF6 and comparisons of the potentials with the earlier values were made. The resulting potentials were used to predict the diffusion coefficient for Kr—Ne.